INNOVATION OF ORGANIZATION MODEL FOR INTEGRAL RURAL DEVELOPMENT - SERBIA CASE STUDY - Vladimir, Nikolić; Ivaniš, Marko; Stevović, Ivan (Economics of Agriculture, 2014)
The experience of the EU in the way of stimulating rural development has been accepted as a starting position in Serbia. The level of economic growth, even in rural areas, despite efforts is not at the desired level. Ways to stimulate rural development process are researched deductively on the example of two municipalities in Sumadija, Serbia. The result of the research pointed to the need to specify the policy of integrated rural development of the municipality and the need to innovate the existing models of organization. It is concluded that the policy of rural municipalities should be directed to: active access to fnance, identity politics, and continuing education. Innovation in the organization involves: an Initiative team who prepare the documentation as a basis for decision-making, implementation of agricultural incubator (a symbiosis of business, technology and incubator for a quality management system), and establishing a system of vertical mergers.